Reliable emergency data transmission using transmission mode selection in wireless body area network. Issue 1 (1st January 2018) - Abdulmohsin Hammood, Dalal; Rahim, Hasliza A; Alkhayyat, Ahmed; Ahmed, R. Badlishah; Abbasi, Qammer H.
Abstract: The main differences between wireless body area network (WBAN) and wireless sensor network are the sensors in WBAN distributed on the human body; therefore, body posture, clothing, muscle movement, body temperature, and climatic conditions generally influence the links between sensors and destination. Second, data gathered by the sensors are related to human life; therefore, it is important to make sure that the gathered data should be delivered to destination efficiently. Hence, in some cases, single-hop transmission or direct transmission mode (DTM) is not sufficient to deliver the data to the destination. In this paper, we proposed an emergency-based cooperative communication protocol for WBAN, named as Emergency Data Transmission using Transmission Mode Selection (ED-TMS) protocol based on the IEEE 802.15.6 CSMA. First, a complete study of a system model is inspected in terms of channel path loss, successful transmission probability, and the outage probability. Second, a mathematical model of the proposed protocol, end-to-end delay, and throughput with relay selection (RS) is derived. Third, RS is utilized along with ED-TMS, which makes only the best relay participate in cooperation in a distributed manner. The design objective of the ED-TMS is to reduce end-to-end delay and enhance the throughput of direct transmission and traditional cooperative communication. The simulation and numerical results show that the ED-TMS can enhance network performance under general conditions compared to DTM IEEE 802.15.6 CSMA and benchmark. The end-to-end delay reductions of ED-TMS with RS with respect to DTM, mutual information incremental cooperative communication, and ED-TMS without RS are 24.5%, 28%, and 30%, respectively.